A resectorization of fire brigades in the north of Portugal - Lima, Margarida (2021)
Sectorization can be regarded as a division of a territory into smaller regions to deal with a complex problem involving multiple-criteria. Resectorization intends to achieve another sectorization, according to some new conditions but avoiding substantial changes. An example of this can be the distribution of geographical areas by fire brigades. In Portugal, fire brigades must protect and rescue the population in the areas surrounding their fire stations. So we will use the current sectorization, the geographic and population characteristics of the areas and the fire brigades’ response capacity to provide an optimised resectorization, in order to decrease rescue time. To achieve that, we will use a decision support system using different optimisation methods, such as Non-dominated Sorting Genetic Algorithm (NSGA II), which provides an effective sectorization concerning compactness and equilibrium criteria.